2015
DOI: 10.1159/000381324
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer and Sarcoidosis: Case Series and Review of the Literature

Abstract: Background: Sarcoidosis is a chronic inflammatory disease of unknown etiology, which can involve different organs and systems. Accordingly, sarcoidosis can mimic breast cancer, making the differential diagnosis very difficult. Case Report: 5 patients with a diagnosis of both sarcoidosis and breast cancer followed by the Rabin Medical Center between January 1993 and June 2012 were enrolled in this study. Additionally, a comprehensive literature review which identified 104 patients diagnosed with breast cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 56 publications
(65 reference statements)
1
25
0
2
Order By: Relevance
“…In 22% the cancer presented first, and in 10% both diseases occurred within less than one year of each other [8].…”
Section: Discussionmentioning
confidence: 98%
“…In 22% the cancer presented first, and in 10% both diseases occurred within less than one year of each other [8].…”
Section: Discussionmentioning
confidence: 98%
“…They have been attributed to tumour-derived antigens provoking CD4+ T lymphocyte activation and granuloma formation and have identical histological appearances and cellular composition to granulomas in sarcoidosis 5 6. Pragmatically, sarcoid-like reactions are diagnosed when there is an identifiable precipitant, histological evidence of non-caseating granuloma and a lack of other features of sarcoidosis, although such features are not well defined 7. Furthermore, patients with sarcoid-like reactions typically have normal vitamin D, calcium and ACE concentrations, without cardiac or central nervous system involvement 8.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chen et al reported 5 cases of sarcoidosis and breast cancer median age of whom was 49 years old when sarcoidosis was diagnosed. The authors suggested that an association between two diseases is uncommon and should be confirmed histologically [ 6 ]. Schweitzer et al reported 10 such cases, where sarcoidosis was diagnosed at 61 years old females, on average 4 years after breast cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%